2017
DOI: 10.1002/bjs.10601
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of management of chronic pain after surgery

Abstract: BackgroundPain present for at least 3 months after a surgical procedure is considered chronic postsurgical pain (CPSP) and affects 10–50 per cent of patients. Interventions for CPSP may focus on the underlying condition that indicated surgery, the aetiology of new‐onset pain or be multifactorial in recognition of the diverse causes of this pain. The aim of this systematic review was to identify RCTs of interventions for the management of CPSP, and synthesize data across treatment type to estimate their effecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
57
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(67 citation statements)
references
References 120 publications
(255 reference statements)
2
57
0
1
Order By: Relevance
“…However, continued pain at or near the surgical site lasting 3-6 months or longer is considered to be a distinct adverse outcome, which has been defined as 'persistent' or 'chronic' post-surgical pain [1,3]. Chronic or persistent pain is a common problem following a wide range of surgery types and has been found, in both cross-sectional and longitudinal studies, to have substantial negative psychological effects that reduce quality of life [4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, continued pain at or near the surgical site lasting 3-6 months or longer is considered to be a distinct adverse outcome, which has been defined as 'persistent' or 'chronic' post-surgical pain [1,3]. Chronic or persistent pain is a common problem following a wide range of surgery types and has been found, in both cross-sectional and longitudinal studies, to have substantial negative psychological effects that reduce quality of life [4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…The negative impact of persistent pain following surgical treatment for breast cancer is a particularly important clinical problem because (1) the prevalence of persistent breast pain (PBP) is relatively high compared to other types of surgery [9]; (2) traditional approaches to managing persistent pain (e.g., long term opioids) are increasingly recognized as being ineffective in relieving pain and are accompanied by problematic side effects [5,10]; (3) there are millions of breast cancer survivors around the world [11,12]; and, 4) PBP has substantial negative psychological sequelae [4,11]. In a widely cited nationwide cross-sectional study (n ¼ 3253) from Denmark, 47% of women reported having pain in the surgical area two to three years after undergoing a mastectomy or breast-conserving surgery for primary breast cancer, and 13% reported severe pain [13].…”
Section: Introductionmentioning
confidence: 99%
“…The aim of this trial is to evaluate the effects of a treatment that could potentially relieve pain and improve physical performance as well as provide education to assist patients in handling their chronic pain and disability. This is of definite importance since no other randomized controlled trial has been conducted regarding exercise as treatment for chronic pain after TKA [12,13]. The trial builds on the presence of sensitization in several studies examining painful knee OA and chronic pain after TKA [7,[43][44][45][46] and evaluates if it is possible to modulate sensitization outcomes by using NEMEX-TJR in combination with PNE.…”
Section: Discussionmentioning
confidence: 99%
“…For patients suffering from chronic pain after TKA, no such guidelines or standardized treatment regime exist. This is emphasized in two recent systematic reviews, summarizing the evidence regarding the treatment of chronic pain after TKA and reporting the absence of randomized controlled trials evaluating the effects of exercise therapy and other treatments [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…The secondary outcome of this review was adverse events, but reporting was lacking. The poor quality of adverse event reporting in surgical trials is recognised,85 and standardisation is required to improve quality and reduce heterogeneity, particularly in orthopaedics. Although patient reported outcomes are frequently considered to be at high risk of bias, we considered them to be appropriate in this review where questionnaires were completed over 6 months after a presurgical intervention.…”
Section: Discussionmentioning
confidence: 99%